Narrative, Meaning, and Multispecies Ethical Ontologies - McCormack, Brian (Humanimalia, 2019)
In this essay, I draw out and develop some key points of connection and overlap between Val Plumwood's dialogical ethical ontology and Jakob von Uexküll's Umwelt theory. Plumwood makes a convincing case for extending a form of narrative subjectivity beyond the human. Uexküll's theoretical biology has been employed in efforts to build on Plumwood's work (by van Dooren and Rose for example), yet such an ethical strategy raises difficult questions of representational accuracy. I address these questions in the second part of the essay, drawing mainly on David Herman's recent work on narratology beyond the human. Articulating a cultural ontology that recognizes the human as part of a broader ecology of selves entails careful experimentation with notions of nonhuman animal narrative.